Sonya Marmeladova – Paradox of Female Power? - Filová, Simona (Mundo Eslavo, 2017)
The paper aims to study the character of Sonya Marmeladovova in Dostoevsky’s novel Crime and Punishement namely through the prism of feminist literary theory. Almost all relationships in Crime and Punishment are determined by the bond of power or let us say unceasing struggle for dominance. Female characters in certain situations resign, Sonya represents the extreme image of this phenomenon, she seems to be untied of that apparently necessary human condition. On the other hand Sonya’s love is said to be the power that saved Rodion Raskolnikov, that is led him to distinct moral principles based on christian faith and ethics. Regarding this verbalization Sonya could be understood as guiding element, leader, the mightier, who enforced her will. However the text indicates rather the situation when every rivalry for the couple is over. But still Sonya (as probably the most outstanding case of female characters in Dostoevsky’s texts) as contrasted to majority of male characters represents person who thanks to strong anchorage in ethic principles and spiritual notions like makefast shows some constant spot in the sea full of rational dilemmas and doubts that torment usually just men in Dostoevky’s works. Dostoevsky seems to emphasise the power of women, the magnitude of their loayality and love, that has noticeably rather the maternal shapes.